IXNH - Walking in the footsteps of the pioneer of Aegean archaeology in celebration of the 200th anniversary of the birth of Heinrich Schliemann: proceedings of the 19th International Aegean Conference/19e Rencontre égéenne internationale, Centro Internazionale per la Ricerca Sulle Civiltà Egee 'Pierre Carlier', Comune Di Oristano e Fondazione Oristano, Università degli Studi Di Sassari, May 10-14 2022 - Laffineur, Robert; Perna, Massimo (Aegaeum, 2024)
To honor the memory of the father of Aegean archaeology and celebrate the 200th anniversary of his birth, the best way was undoubtedly to show the advances that have been made over the last hundred and fifty years of excavations at the sites Heinrich Schliemann first explored, as well as on other sites he just visited, in Italy - including Sardinia - and in Greece - Therasia in the Santorini caldera -, keeping in mind that these first steps he took also mark the very beginnings of Aegean archaeology.0The 19th International Aegean Conference / 19e Rencontre égéenne internationale focused therefore on evaluating - albeit very partially - the results of the extensive fieldwork conducted by so many teams at Troy, Mycenae, Tiryns, and Orchomenos, walking in the footsteps of the pioneer. To fully appreciate the progress made since Schliemann?s explorations, various aspects were considered, such as topography and environment, architecture, artistic and craft production, social organization, religious beliefs and practices, means of subsistence and sources of supply, as well as echoes in later textual sources. The latter approach was fundamental in Schliemann?s thinking and methodology. It is first addressed in the keynote lecture and then discussed, in the same perspective of appraising the evolution and achievements of scientific research during a century and a half.0The Centro Internazionale per la Ricerca sulle Civiltà Egee, in Oristano, Sardinia, where the conference took place is dedicated to the late Pierre Carlier, who devoted an important part of his career and research to the evocations of Aegean material testimonies in later textual sources. The IXNH conference also pays tribute to him
Keywords: Schliemann, Heinrich -- 1822-1890 -- Congresses; Aegean Islands (Greece and Turkey) -- Antiquities -- Congresses; Konferenzschrift -- 2022 -- Oristano; Antike; Kultur; Archäologie; Ägäis